The Effect of Nitrogen Fertilizer Based on Pocket Fertigation on Growth and Production of Tomato (Solanum lycopersicum L.) - Bayu Dwi Apri Nugroho; Chusnul Arif; Yusuf Wibisono; Andrianto Ansari (AGRIVITA Journal of Agricultural Science, 2023)
The tomato (Solanum lycopersicum) is considered a significant horticultural crop in Indonesia and is widely consumed by the local population. It should be cultivated by more efficient water irrigation methods, such as pocket fertigation. This study aims to determine the effect of pocket fertigation-based nitrogen fertilizer treatment on the growth and yield of tomato plants. Three different treatments of fertilizers, including without chemical fertilizer as control (P0), 200 kg/ha of urea fertilizer (P1), and 200 kg/ha of ZA fertilizer (P2), are applied by utilizing pocket fertigation. The tomato plant is cultivated under 24-30oC of daily air temperature, 25.6-28.9oC of soil temperature, and 68-201 W/m² of solar radiation recorded by an automatic weather station. The results show that treatments do not significantly affectplant height, number of branches, root volume, number of fruits, fruit weight per plant, fruit color index, fruit hardness, Brix, and consumption index. However, P1 increases yield and fruit quality more efficiently, while P2effectively increases plant weight. Further research needs to regard the optimal dosage of Ureaand ZA in optimizing the yield and quality of fruits.